Awareness and practice of anemia prevention among antenatal women in Hospital Universiti Sains Malaysia - Asri, Siti Syakirah Mohd (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2022)
Anemia is a serious global public health problem that particularly affect young children and pregnant women. It is a huge contributor to maternal mortality. The World Health Organization (WHO) estimates that 40% of pregnant women worldwide are anaemic. This research aimed to determine the level of awareness and practice of anemia prevention among antenatal women. A cross-sectional study was conducted in the obstetrics ward and Obstetrics and Gynecology Clinic of Hospital Universiti Sains Malaysia from April to May 2022. A total of 106 participants was conveniently selected and data were collected using structured self-administered questionnaire and analyzed with the Statistical Package of the Social Sciences version 26.0. Pearson’s correlation test and Pearson Chi-Square was used for data analysis. Result showed that the level of awareness of anemia among antenatal women was moderate (n=43, 40.6%) and the majority have high practice of anemia prevention (n= 105, 99.1%). The study showed no significant association between awareness and practice of anemia prevention. The study also revealed no significant association between demographic data and the practice of anemia prevention. In conclusion, antenatal women generally lack of awareness towards anemia. There is a need for public education to provide information about anemia in pregnancy, thus decreasing the risk of maternal and neonatal mortality and morbidity.